2007
DOI: 10.1071/wf06109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of plant functional types under simulated fire regimes

Abstract: Abstract. In spite of enormous fire suppression advances in Mediterranean countries, large high-intensity fires are still common. The effects on vegetation structure and composition of fire and fire regime changes at large spatial and temporal scales are poorly known, and landscape simulation models may throw some light in this regard. Thus, we studied how the abundance, richness, and spatial distribution of the different plant types are sensitive to the frequency, extent and spatial distribution of wildfires,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
1
36
0
1
Order By: Relevance
“…Several studies have confirmed that the recovery rate of scrub cover after fire was quite rapid, often exceeding the pre-fire biomass amount (Hernandez-Clemente et al, 2009;Roder et al, 2008;Viedma et al, 1997). Simulation models such as FATELAND and BROLLA have shown an increase in shrublands as a response to increased fire frequency, creating a state of successional stagnation which may enhance the positive shrub-fire feedback (Pausas, 1999;Pausas and Lloret, 2007) (Fig. 3).…”
Section: Fire Frequency Is Higher In Previously Burned Areasmentioning
confidence: 95%
“…Several studies have confirmed that the recovery rate of scrub cover after fire was quite rapid, often exceeding the pre-fire biomass amount (Hernandez-Clemente et al, 2009;Roder et al, 2008;Viedma et al, 1997). Simulation models such as FATELAND and BROLLA have shown an increase in shrublands as a response to increased fire frequency, creating a state of successional stagnation which may enhance the positive shrub-fire feedback (Pausas, 1999;Pausas and Lloret, 2007) (Fig. 3).…”
Section: Fire Frequency Is Higher In Previously Burned Areasmentioning
confidence: 95%
“…Indeed, several studies have shown that tree cover was the most relevant variable to explain differences in the characteristics of Mediterranean plant communities (Gondelis et al, 2008;Eugenio and Lloret, 2006;Eugenio et al, 2006;Pausas and Lloret, 2007;Kazanis and Arianoutsou, 1996;Clemente et al, 1996). In these studies, fire intervals ranging from 2 to 10 years negatively affected most ecosystem attributes such as soil organic matter, and led to structural simplification of the vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Eugenio et al (2006), fire recurrence is defined as the number of fire events occurring at a site during a given period of time. Many studies have only taken into account the effect of the number of fires (Gondelis et al, 2008;Eugenio and Lloret, 2006;Eugenio et al, 2006;Pausas and Lloret, 2007;Kazanis and Arianoutsou, 1996;Clemente et al, 1996). However, the time interval between two successive fires can also have different impacts on the vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is support for the idea that plant flammability may have played an evolutionary role in some species (Mutch 1970). Given the paucity and the infeasibility of conducting extensive field experiments, simulation modeling is one of the few ways we can investigate patterns of plant traits (e.g., Pausas and Lloret 2007) or the degree to which plants may alter their own probabilities of burning at local (e.g., Bond and Midgley 1995) and landscape scales (e.g., Moritz et al 2005). Assessing the sensitivities of fire-related models may thus lead to insights in both scientific and management contexts.…”
Section: Discussionmentioning
confidence: 99%